2011
DOI: 10.1021/jp207682s
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Refractive Index Sensitivity of Supported Silver Nanocube Monolayers

Abstract: The refractive index (RI) sensitivity of extinction spectra was compared experimentally for silver nanocubes in solution and in supported monolayers prepared by the Langmuir technique. The size of the nanocubes, RI of supporting dielectric substrate, and monolayer surface pressure were used as variables in refractive index sensing optimization. The dipolar plasmon modes of the colloidal nanocubes were found to have the highest RIS values of 176, 361, and 480 nm/RI units for 40, 80, and 130 nm cubes, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Nanocube substrates were prepared according to the procedure reported previously. 16 Briefly, NIMA 311D trough, filled with Milli Q water (18.2 MΩ cm) was used to prepare the Langmuir films of different NC samples. In order to form monolayers an appropriate amount of each sample was transferred into chloroform and deposited onto the surface of the water using a microsyringe.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Nanocube substrates were prepared according to the procedure reported previously. 16 Briefly, NIMA 311D trough, filled with Milli Q water (18.2 MΩ cm) was used to prepare the Langmuir films of different NC samples. In order to form monolayers an appropriate amount of each sample was transferred into chloroform and deposited onto the surface of the water using a microsyringe.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As the nanocube approaches the glass substrate, the dipolar and the quadrupolar modes become more resolved. 30,36 Also shown are the field intensities of the hybrid quadrupolar (Q) mode and the dipolar (D) mode where the white horizontal line represents the substrate (Figure 1.9B, C). 33 These modes are spatially separated on the nanocube.…”
Section: Plasmonicsmentioning
confidence: 99%
“…Recently, it has been found that the interaction of "dark states" and "bright states" in metamaterial and plasmonic structures can also form Fano resonances [3][4][5][6]. Due to the sharp lineshape, a slight perturbation in local environment can cause a considerable change in transmission, reflection, or extinction spectrum [7], which is very helpful especially for applications such as sensor and modulator [8,9].…”
Section: Introductionmentioning
confidence: 99%